2022
DOI: 10.3390/cancers14030555
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose Metabolism, Anti-Diabetes Medications, and Risk of Thyroid Cancer

Abstract: The prevalence of obesity is progressively increasing along with the potential high risk for insulin resistance and development of type 2 diabetes mellitus. Obesity is associated with increased risk of many malignancies, and hyperinsulinemia has been proposed to be a link between obesity and cancer development. The incidence of thyroid cancer is also increasing, making this cancer the most common endocrine malignancy. There is some evidence of associations between obesity, insulin resistance and/or diabetes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 172 publications
0
7
0
Order By: Relevance
“…We also reported that, in addition to congenital hypothyroidism, these mice develop neonatal diabetes and hypoinsulinemia [39,58]. IGF-1 and insulin, together with TSH, have been reported to play a critical role in the regulation of gene expression and proliferation in thyroid follicular cells [51][52][53][54][55][56] raising the possibility that the pancreatic phenotype, including hypoinsulinemia, and conceivably changes in other tissues in ubiquitous Glis3-de cient mice might in uence the function and gene expression in thyroid follicular cells. This hypothesis was supported by observations showing that in contrast to ubiquitous Glis3-KO(LID) mice, thyroid follicular cell proliferation, expression of cell cycle genes, including Ccnb1, Ccnb2, and Cdca2, and activation of the mTOR, a pathway that promotes cell proliferation, were not repressed in Glis3-Pax8Cre(LID) mice but induced to a similar degree as in WT(LID) mice (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…We also reported that, in addition to congenital hypothyroidism, these mice develop neonatal diabetes and hypoinsulinemia [39,58]. IGF-1 and insulin, together with TSH, have been reported to play a critical role in the regulation of gene expression and proliferation in thyroid follicular cells [51][52][53][54][55][56] raising the possibility that the pancreatic phenotype, including hypoinsulinemia, and conceivably changes in other tissues in ubiquitous Glis3-de cient mice might in uence the function and gene expression in thyroid follicular cells. This hypothesis was supported by observations showing that in contrast to ubiquitous Glis3-KO(LID) mice, thyroid follicular cell proliferation, expression of cell cycle genes, including Ccnb1, Ccnb2, and Cdca2, and activation of the mTOR, a pathway that promotes cell proliferation, were not repressed in Glis3-Pax8Cre(LID) mice but induced to a similar degree as in WT(LID) mice (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The increase in glucose uptake across the plasma membrane, which is necessary to support energy needs for cancer development, was reported in thyroid cancer cells, in which an elevated expression of GLUT1 and GLUT3 could be mainly involved in the oncogenesis process [125]. Additionally, hyperglycemia can affect cancer cellular growth and proliferation via many other mechanisms, such as increasing oxidative stress and inflammatory cytokines, the protection of cancer cells from apoptosis, the stimulation of cell motility, and adhesion [122].…”
Section: Thyroid and Type 2 Diabetesmentioning
confidence: 96%
“…An association between THs and diabetes has also been demonstrated in pregnant women with gestational diabetes or pre-existing T2D, with possible adverse effects for both maternal and fetal health [120,121]. The relationship between IR and/or T2D, obesity, and thyroid cancer has been recently explored and, although the etiology of such an association is unclear, it may involve high insulin levels, increased body fat, hyperglycemia, and antidiabetes medications including exogenous insulin use [122]. As for anti-diabetes drugs, the role of metformin in thyroid cancer remains controversial due to its growth-inhibitory effects, which are implicated in AMPK-related pathways, the mammalian target of NF-κB, rapamycin and mitochondrial glycerophosphate dehydrogenase [123].…”
Section: Thyroid and Type 2 Diabetesmentioning
confidence: 99%
“…Only few clinical studies up to now evaluated the relationship between insulin therapy and thyroid cancer risk ( Kushchayeva et al, 2022 ). A 2014 studies based on data from the reimbursement databases of all Taiwanese diabetic patients from 1996 to 2009 evaluated the incidence of thyroid cancer according to the use, duration and dosage of therapy with human insulin.…”
Section: Insulinmentioning
confidence: 99%